Variables Affecting the Preparation and Characterization of Axitinib as Oral Niosmoes - Ibtihal Abdulkadhim Dakhil; Nidhal K. Maraie (College of Pharmacy University of Baghdad, 2024)
Axitinib is anticancer drug act on different solid tumors by inhibtion protein kinase enzyme which is responsible for support the tumors with blood demand. Due to its low solubility, it has low bioavailability when given orally also it is affected by liver metabolism. Axitinib formulated as non-ionic vesicles (niosomes) for the first time to study the effect of different variables on the in vitro behaviour of vesicles in a hope to improve drug oral bioavailability.       Niosomal dispersion formulas were formulated by diverse techniques via multiple kinds of surface-active agent (tween also span), cholesterol and dicetyl phosphate then evaluated for visual appearance, efficiency of drug entrapment (EE%), size of the vesicles, poly dispersity index, zetapotential, viscosity, invitro drug release and study the vesicles morphology by FE-SEM. Many variables effect on EE% were studied such as effect of surfactant amount and type, effect of surfactant combination, impact of various ratios of cholesterol, impact of DCP in various amount , effect of preparation method and effect of sonication time.       The results showed that the EE% between (50.97%-98.24%), the particle size was found within the range (64.5 nm - 530.79 nm), zeta potential which was between ( -16.6 to -31 mV), polydispersity index (PDI) <1 and viscosity between (584 - 889.6) centipoise. The niosomal dispersion F1 which contained 1:1 weight ratio (span60: cholesterol) was found with high EE% (96.5±0.16%), smallest particle size (64.5±0.5 nm), highest drug release (100%) of drug released at the end of 4 hours and FE-SEM photograph showed that niosomes were spherical with no aggregation and had a smooth surface.           The results showed that thin film hydration method with sonication for four minutes was the best method for preparation of axitinib niosomes, the type and amount of surfactants used, cholesterol ratio, stabilizer and the time of sonication had a substantial effect on EE%, the size of the vesicles as well as drug release; which were investigated so as to optimize the niosomal dispersion of anti-tumour drug reaching to an optimum formula that may improve drug bioavailability. Key words: Axitinib, Anticancer, Vesicles, Surfactants, Invitro behaviour, Entrapment efficiency.